The Impact of Home Work Environment, Team Interaction, and Online Training on Employee Productivity in a Hybrid Work Model in the Indonesian Education Sector - Evi Susanti; Desty Endrawati Subroto; Nanda Hidayati; Tri Astuti; Andi Aco Agus (Westscience Press, 2024)
This research examines the impact of the home work environment, team interaction, and online training on employee productivity within the Indonesian education sector operating under a hybrid work model. A quantitative analysis was conducted, involving 160 employees from various roles within educational institutions. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3 software. The findings reveal significant positive relationships between the home work environment, team interaction, online training, and employee productivity. Conducive home work environments, robust team interactions, and effective online training programs emerge as critical factors in enhancing workforce performance in remote and hybrid work settings. The study contributes to a nuanced understanding of contemporary work dynamics and offers practical insights for organizational strategies aimed at fostering productivity in the Indonesian education sector.